Using Customer Satisfaction as a Mediating Variable to Boost Service Quality and Build Trust in Repeat Business - Febriana Sakina; Muhammad Yafiz (Jurnal Manajemen Bisnis, 2023)
The purpose of this research is to identify the moderating effects of service quality, confidence in customer loyalty, and satisfaction. Quantitative survey methodology is used in this kind of study. A total of one hundred residents of Tanjung Pura participated as respondents in this survey. In this study, we employ SPSS version 26 to conduct a multiple linear regression analysis and a Sobel test. The findings indicate that while service quality does not positively or significantly affect customer loyalty, trust does. The level of client satisfaction is significantly impacted by the quality of the service provided. Consumers are more satisfied after having their trust in a company restored. There is a statistically substantial correlation between client loyalty and satisfaction levels. One way in which customer satisfaction can moderate the relationship between service quality and loyalty is through the lens of referrals. Trust can increase consumer loyalty, and satisfaction can moderate this relationship.